#TITLE_ALTERNATIVE# - KURNIASIH (NIM : 13206057); Pembimbing : Dr Achmad Munir, FRIDA
One of the technology used for radar absorber is Salisbury screen, that is a resistive sheet positioned on /4 from a conducting metal ground plane. It cancel the reflected signal by destructive phasing exist at the front of the resistive sheet. Nowadays, however artificial magnetic conductor (AMC) can be applied to reduce the thickness of an absorber. AMC is a physical approximation of perfect magnetic conductor (PMC) but with zero degree reflection properties only in a narrow frequency band. In this final project, the effect of hexagonal patch on the characteristic of radar absorber is numerically investigated. The unit cell as the form of a double periodic array of infinite extent is analized. The investigation is carried out on two types of dielectric substrate, they are Taconic CER-10 and FR4-Epoxy. When the Taconic CER-10 is used as a dielectric substrate, the resonance frequency is around 3.3 GHz, and the hexagonal patch is 7.5056 mm. While the FR4-Epoxy substrate, the resonance frequency in the range of 2.5 to 2.7 GHz, and the hexagonal patch is 16.17 mm. Then, the influence of the dimension of unit cell to the resonant frequency and reflection coefficient is analyzed. Incorporation of an external resistive element onto the surface is also analyzed. It is shown that external resistive element incorporatid at the side perpendicular to the electric field give no effect to the magnitude of reflection coefficient on the microwave radar absorber. The analysis of the use of hexagonal patches in several different types of dielectric substrate is also investigated. By analyzing these characteristics, the desired absorber dimensions primarily associated with the thickness can be determined.